Healthcare workers' perspectives on coronavirus testing availability: a cross sectional survey - Elena Byhoff; Jessica K. Paulus; Rubeen Guardado; Julia Zubiago; Alysse G. Wurcel (BMC, 2021)
Abstract Background Studies on the impact of the novel SARS-CoV-2 virus (COVID) for healthcare workers (HCWs) rarely include the full spectrum of hospital workers, including less visible patient support roles. In the early days of the pandemic, COVID testing was preferentially available to HCWs. The objective of this study was to understand how individual experiences for all HCWs during the pandemic were associated with perceptions of access to, and receipt of COVID testing . Methods All hospital employees (n = 6736) in a single academic medical center in Boston, Massachusetts were invited to participate in a cross-sectional survey regarding perceived access to, and receipt of COVID testing during the first wave of the pandemic (March - August 2020). Responses were linked to human resources data. Log binomial univariate and multivariable models were used to estimate associations between individual and employment variables and COVID testing. Results A total of 2543 employees responded to the survey (38 %). The mean age was 40 years (± 14). Respondents were female (76 %), white (55 %), worked as nurses (27 %), administrators (22 %) and patient support roles (22 %); 56 % of respondents wanted COVID testing. Age (RR 0.91, CI 0.88-0.93), full time status (RR 0.85, CI 0.79-0.92), employment tenure (RR 0.96, CI 0.94-0.98), changes in quality of life (RR 0.94, CI 0.91-0.96), changes in job duties (RR 1.19, CI 1.03-1.37), and worry about enough paid sick leave (RR 1.21, CI 1.12-1.30) were associated with interest in testing. Administrators (RR 0.64, CI 0.58-0.72) and patient support staff (RR 0.85, CI 0.78-0.92) were less likely than nurses to want testing. Age (RR 1.04, CI 1.01-1.07), material hardships (RR 0.87, CI 0.79-0.96), and employer sponsored insurance (RR 1.10, CI 1.00-1.22) were associated with receiving a COVID test. Among all employees, only administrative/facilities staff were less likely to receive COVID testing (RR 0.69, CI 0.59-0.79). Conclusions This study adds to our understanding of how hospital employees view availability of COVID testing. Hazard pay or other supports for hospital workers may increase COVID testing rates. These findings may be applicable to perceived barriers towards vaccination receipt.